Perspectives nationale et internationale dans l’étude du PCF et du PCI - Sollai, Luca (Émulations – revue des sciences sociales, 2018)
The concepts of "national" and "international" are crucial in the study of the French Communist Party and the Italian Communist Party. The two most important communist parties in Western Europe have always tried to reconcile their national political proposals with USSR international and geopolitical issues. The synthesis was not always easy, and this difficulty emerges in the historiographical debate of the two parties. A conflictual approach has been developed by historians of both parties, and these two concepts have not been analyzed as two aspects of a global perspective, but rather as opposed one to another. After examining the thesis of some historians, we propose an organic and more neutral approach, using as a case of study the utilization of national symbols by both parties. We chose a comparative approach because the geopolitical and historical situation of the two parties presented some similarities. Also, in both cases, we can observe, with some differences, the affirmation of two conflicting historiographical school of thoughts.
Number: 26
Keywords: =CL; PCF; PCI; communisme; international; national